2016
DOI: 10.1146/annurev-food-041715-033243
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine: Friend or Foe?

Abstract: The debate on the safety of and regulatory approaches for caffeine continues among various stakeholders and regulatory authorities. This decision-making process comes with significant challenges, particularly when considering the complexities of the available scientific data, making the formulation of clear science-based regulatory guidance more difficult. To allow for discussions of a number of key issues, the North American Branch of the International Life Sciences Institute (ILSI) convened a panel of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 129 publications
3
43
0
3
Order By: Relevance
“…The biological effects of caffeine are heterogeneous ( Figure 3). On the one hand, it has been suggested that low doses of caffeine could exert beneficial activities on endothelial function [35,36], in inflammatory processes by reducing some pro-inflammatory cytokines [36,37], and in the improvement of cognitive faculties, as well as providing protection against dementia [35,38]. However, clinical trials conducted in humans have suggested that caffeine is not responsible for the certain beneficial properties observed in caffeinated beverages, like the anti-inflammatory effects of coffee [39,40].…”
Section: Caffeinementioning
confidence: 99%
“…The biological effects of caffeine are heterogeneous ( Figure 3). On the one hand, it has been suggested that low doses of caffeine could exert beneficial activities on endothelial function [35,36], in inflammatory processes by reducing some pro-inflammatory cytokines [36,37], and in the improvement of cognitive faculties, as well as providing protection against dementia [35,38]. However, clinical trials conducted in humans have suggested that caffeine is not responsible for the certain beneficial properties observed in caffeinated beverages, like the anti-inflammatory effects of coffee [39,40].…”
Section: Caffeinementioning
confidence: 99%
“…In a recent study, Liu et al found that normal, infarcted, ischemic myocardium can be differentiated by native T1 mapping at rest and during adenosine stress because these tissues classes exhibit distinctive T1 profiles. Compared to resting conditions, myocardial T1 values during adenosine stress increased approximately 6 % both at 1.5 and 3.0T field strengths in of variation between individuals are frequency of caffeine intake, concurrent cigarette smoking and genetic variations in the adenosine receptors and downstream signaling cascade proteins [4]. As demonstrated by Kuijpers et al, native T1-mapping seems capable of detecting the blunting effects of caffeine consumption on adenosine-induced myocardial hyperaemia.…”
mentioning
confidence: 92%
“…Caffeine (1,3,7-trimethylxanthine) is one of the most widely consumed stimulants worldwide with over 80 % of the US population reporting daily intake [4]. Individuals primarily consume caffeine for a variety of behavioral effects such as changes in mood, energy and alertness [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations